Analisis Undang-Undang No.3 Tahun 2020 yang Berpotensi Merugikan Masyarakat dan Lingkungan Berdasarkan Prinsip Sustainable Development Goals - Basthotan Milka Gumilang; Sherly Oktariani; Tari Suswinda (Jurnal Hukum Lex Generalis, 2022)
The Mineral and Coal Law currently used is Law No. 3 of 2020 concerning Mineral and Coal Mining, a change to Law No. 4 of 2009 concerning Mineral and Coal Mining. This Act is a tool for regulating the mining of minerals and coal and its various permits. With the aim that the state obtains huge profits from mining products that can be used for the welfare of the people. But in reality, currently, there are several crucial articles that have the potential to harm the community and also the environment in Law No. 3 of 2020 and the Manuscript of the Job Creation Law No. 11 of 2020 in the Mineral and Coal Mining Sector in lieu of the Mineral and Coal Law.